PRODUCTION OF BASIC MATERIAL CARRAGEENAN HYDROGEL USING POLYMER BASED POLYVINYL ALCOHOL (PVA) - Nurrahmi, Febi; Siregar, Yusni Ikhwan; Fransiska, Dina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Indonesia has a local source of raw materials based on natural polymer hydrogel, ie seaweed the number and type of abundant. One of processed seaweed products of high economic value is carrageenan. Synthesis of carrageenan-based hydrogels prepared from local seaweed is still not widely used. Based on the properties that can proved a cooling effect and moisture of water is also restricted by the hydrogel. This research aims to develop the use of carrageenan from seaweed into a hydrogel wound dressings. The current study analysis further the quality of the resulting hydrogel using κ and τ-carrageenan than the optimal concentration of PVA in producing the hydrogel. Well studied conducted with concentration κ and τ -carrageenan (6:4) 3%, and the addition of PVA polymer concentration formulation (7.5%; 10%; 12.5%; 15%), and irradiated using γ-rays at a dose 15 kGy (dose rate of 2.5 kGy / h). Characterization measured include the value of the ratio swelling, gel fraction and tensile strength. The test results hydrogel formulations with increasing concentration of 12.5% PVA ratio swelling 416.58%, 67.39% gel fraction and tensile strenght of 3.48 kg / cm2.Key words: τ-carrageenan, κ-carrageenan, hydrogels, irradiation, hydrogel, a polymer PVA (Polyvinyl Alcohol)